Food systems science for peace and security: Is research for development key for achieving systematic change? - Liebig, Theresa Ines; Pacillo, Grazia; Osorio, Diego; Läderach, Peter R.D. (Elsevier, 2022)
This paper uses CGIAR research as an example to demonstrate the potential of food systems science to contribute to conflict prevention and peacebuilding. Conflict often arises through a complex process whose triggers and consequences are closely interconnected in feedback loops and linked to climate variability, environmental degradation and food insecurity. Conflicts are often approached from asymptomatic rather than a holistic perspective. We (i) review the literature on climate security to identify conflict pathways and related drivers. This serves as the basis for mapping CGIAR and partner research related to climate security through a portfolio review (ii) and facilitated multidisciplinary expert panel discussions (iii) we then define cross-cutting priorities for the future direction of climate security debates, policies and programmes and link them to the new OneCGIAR strategy.